Cinematic Representation of Chinese-Indonesians’ Trauma in Jason Iskandar The Day The Sky Roared - Sutandio, Anton (Lingua Cultura, 2019)
This research analyzed a contemporary independent Indonesian film entitled The Day the Sky Roared (2015) that was directed by Jason Iskandar. This 10-minute silent film talked about the anxiety of Chinese-Indonesians through the eyes of a mother and her daughter regarding the historical trauma of the May 1998 tragedy. The fact that the film was produced about 17 years after the tragedy suggested the director’s awareness that the trauma remained due to the absence of reconciliation and closure. This research would show how the short film frames the incident and trauma of the Chinese-Indonesians. The research was a combination of trauma studies and film studies that focuses on the visual analysis of the film’s cinematography and mise-en-scene to show the cinematic representation of Chinese-Indonesians’ trauma. The findings show that the portrayal of Chinese-Indonesians still strongly suggests unrelieved psychological discomfort, albeit, at different levels, that is closely related to the traumatic past and the pervasive stereotyping of Chinese-Indonesians.